The Effectiveness of Traditional and Modern Memorization Techniques for Quranic Learning in Indonesia - Adi Chandra Wijaya (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2024)
The process of memorizing the Quran, a revered practice in the Muslim world, employs a variety of methods ranging from traditional oral repetition to contemporary technological aids. The research primarily seeks to identify which techniques yield the highest retention rates and the most profound understanding among students. This study employs a literature review methodology, analyzing a wide array of existing research, articles, and case studies that focus on Quranic memorization techniques. Sources include academic journals, educational reports, and empirical studies conducted in Indonesian madrasas and Quranic schools. By synthesizing findings from these sources, the study offers a comprehensive overview of the strengths and limitations of both traditional and modern memorization strategies. The results of this research indicate that while traditional methods such as rote learning and oral recitation continue to be highly effective in fostering deep memorization, modern techniques incorporating digital tools and interactive learning platforms significantly enhance engagement and accessibility for students. The integration of both methods appears to offer the most balanced and effective approach, combining the thoroughness of traditional practices with the innovation of modern technology